Night Eating Syndrome: Report of a family case. (August 2016) - Sevinçer, Güzin M.; Allison, Kelly C.
Abstract: Night eating syndrome (NES) represents a circadian delay in the pattern of eating. As there are genetic links for other eating- and circadian-based disorders, it is likely that there is a genetic basis for NES as well. We present a family case study of three identified patients and their extensive family history of NES and co-morbid mood disorders. This case report suggested that NES may have a heritable feature, particularly nocturnal ingestions. Of the seven identified cases, four had co-morbid mood disorders, and all descended from a couple with bipolar disorder and delusional disorder. More work is needed to understand the extent of genetic influence on NES, and the relationship between NES and other psychiatric disorders. Highlights: A patient seeking psychiatric services reported having night eating syndrome (NES). Several other family members who engaged in similar patterns of eating were identified. Further assessment of the family identified seven cases of NES and of these, four had co-morbid psychiatric symptoms. All cases experienced nocturnal ingestions as a common symptom. All cases originated from the same couple of origin.